(untitled) (Eurasian Scientific Herald, 2023)
This article focuses not only on language acquisition but also on developing the necessary skills and intercultural competencies to be successful in a multicultural society. In today’s globalized world, the ability to communicate effectively in a foreign language is becoming increasingly important. This is particularly true in higher education, where universities are becoming increasingly diverse and international. While language courses are often offered at universities, there is increasing recognition of the need to go beyond language skills and implement the concept of communicative education abroad